Magnesium-Dependent Promotion of H2O2 Production Increases Ecological Competitiveness of Oral Commensal Streptococci. (July 2020) - Cheng, X.; Redanz, S.; Treerat, P.; Qin, H.; Choi, D.; Zhou, X.; Xu, X.; Merritt, J.; Kreth, J.
The pyruvate oxidase (SpxB)–dependent production of H2 O2 is widely distributed among oral commensal streptococci. Several studies confirmed the ability of H2 O2 to antagonize susceptible oral bacterial species, including caries-associated Streptococcus mutans as well as several periodontal pathobionts. Here we report a potential mechanism to bolster oral commensal streptococcal H2 O2 production by magnesium (Mg 2+ ) supplementation. Magnesium is a cofactor for SpxB catalytic activity, and supplementation increases the production of H2 O2 in vitro. We demonstrate that Mg 2+ affects spxB transcription and SpxB abundance in Streptococcus sanguinis and Streptococcus gordonii . The competitiveness of low-passage commensal streptococcal clinical isolates is positively influenced in antagonism assays against S. mutans . In growth conditions normally selective for S. mutans, Mg 2+ supplementation is able to increase the abundance of S. sanguinis in dual-species biofilms. Using an in vivo biophotonic imaging platform, we further demonstrate that dietary Mg 2+ supplementation significantly improves S. gordonii oral colonization in mice. In summary, our results support a role for Mg 2+ supplementation as a potential prebiotic to promote establishment of oral health–associated commensal streptococci.